The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1007/s11071-022-07217-9
|View full text |Cite
|
Sign up to set email alerts
|

JRP analysis of synchronization loss between signals recording during bubble departures

Abstract: The synchronization between the air pressure fluctuations and the depth of liquid penetration into the nozzle during bubble departures was investigated using joint recurrence quantification analysis. In the experiment, the bubbles were generated from a glass nozzle into distilled water. During the analysis, the recurrent rate coefficients were calculated for the depth of liquid penetration into the glass nozzle and pressure changes in the gas supply system. The study was conducted by two air volume flow rates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In 10 , it was shown that the chaotic character of bubble trajectories is caused by the departed bubble’s shape and liquid flow generated by the moving bubble in the bubble column. Moreover, two groups of phenomena responsible for the chaotic nature of bubble behaviours (the first group—bubble interface oscillations, liquid flow around the needle, and the second group—processes which appear in the gas supply system) are proposed 12 14 . It can be assumed that the liquid flow above the needle can modify the processes that appear in the needle, and consequently, the pressure fluctuation in the gas supply system.…”
Section: Introductionmentioning
confidence: 99%
“…In 10 , it was shown that the chaotic character of bubble trajectories is caused by the departed bubble’s shape and liquid flow generated by the moving bubble in the bubble column. Moreover, two groups of phenomena responsible for the chaotic nature of bubble behaviours (the first group—bubble interface oscillations, liquid flow around the needle, and the second group—processes which appear in the gas supply system) are proposed 12 14 . It can be assumed that the liquid flow above the needle can modify the processes that appear in the needle, and consequently, the pressure fluctuation in the gas supply system.…”
Section: Introductionmentioning
confidence: 99%